Prognostic significance of elevated platelet count (> 200 x 10^9 per L) in BCLC stages B and C of hepatocellular carcinoma: a retrospective multicenter analysis - Munker, Stefan; Rodriguez, Isaac; Bernhart, Kathrin; Khaled, Najib Ben; Findik, Merve; Siegmund, Lisa Katrin; Ye, Liangtao; Reiter, Florian P.; Roessler, Daniel; Nasseh, Daniel; Balcar, Lorenz; Pomej, Katharina; et al. (Journal of hepatocellular carcinoma, 2025)
Evaluating the prognostic role of platelet counts across BCLC stages, adjusted for portal hypertension, to improve individualized patient management with HCC